PP30 The ambulance service and the child and young person's advance care plan: listening to families and professionals. Issue 10 (25th September 2020) - Shaw, Karen; Spry, Jenna; Cottrell, Serena; Cummins, Carole; Fitzmaurice, Nicki; Greenfield, Sheila; Heath, Gemma; Miller, Joshua; Neilson, Sue; Skrybant, Magdalena; Thompson, Paul; Vyse, Janette
Abstract : Background: The Child and Young Person's Advance Care Plan (CYPACP) is a set of resources to help families and professionals agree a plan of care to be followed when a child/young person with a life-limiting condition develops potentially (i) reversible intercurrent illnesses or (ii) life-threatening complications of their condition. It covers clinical, psychosocial and spiritual issues, is designed for use in all environments that the child encounters, and can be used as a resuscitation and/or end-of-life plan. Little is known about the experiences of Ambulance Service staff who receive copies of these plans and may be called upon to follow the recommendations for treatment and resuscitation. Methods: As part of a regional qualitative research study, families who have a CYPACP and members of the ambulance service were invited to share their views and experiences of the CYPACP via an online survey, in focus groups or individual interviews. Underpinned by an interpretative framework, thematic and linguistic analyses are being used to understand the implementation in 'real-world' settings, and how the CYPACP shapes the experience, delivery and quality of care. Results: To date 20 families with a CYPACP and 25 members of the ambulance service have taken part. Analysis is on-going. Preliminary findings show that despite families with CYPACPs having multiple experiences of interactions with the ambulance service, it is rare for ambulance crews to attend a call where a child has a CYPACP in place. Findings also suggest that there are critical points within the process of conveying the information contained within the CYPACP document that could be improved. Conclusion: Following full analysis, it is anticipated that the ambulance services involvement with the CYPACP planning process will be better understood and that improvement strategies, including revision to existing documentation and identification of specific support needs can be made.